The Relevance of the Merdeka Curriculum Vocational School to the Competency Needs in the Construction Field in the Industry - Anisah, Anisah; Iriani, Tuti; Ramadhan, M. Agphin; Yusrina, Yusrina (invotek, 2023)
The issue of curriculum relevance in vocational education is a crucial issue of all time. The relevance of the curriculum has two blades, whether it will be the biggest strength or even the biggest weakness in vocational education. Relevance will link the existing employment potential and the graduate's ability to fulfill the job requirements. This research aims to determine the relevance of the independent vocational school learning curriculum, especially in the field of construction, with the competencies needed in the world of work. This research uses a qualitative approach with participants being teachers in the field of study, especially construction and leaders/heads/managers in companies. Data collection was carried out through a Focus Group Discussion (FGD). The questions in the FGD consisted of open-ended questions to find out participants' answers in detail. The research results show that there is relevance between the Merdeka Curriculum and the needs of industry, especially in the building construction sector. Vocational school graduates generally have opportunities in small-scale construction industry services and efforts to increase relevance between schools and industry are to increase cooperation and increase teacher competence.